The involvement of TB counselors increased the case finding figures of child TB in Fanayama and Maniamolo Sub-districts in South Nias Regency - Rachmat Willy Sitompul; Dewi Sukowati; Pedaman Halawa (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: The number of TB case detection rate in 2017 in South Nias Regency is 18%. This figure is still far from the national target of TB case detection rate. In addition, the absence of data for child TB cases is another worrying problem considering that only 9% of TB patients in South Nias are treated properly according to standards.Method: Since 2015, Wahana Visi Indonesia (WVI) in collaboration with the South Nias Health Office has trained TB counselors in 8 villages in the work area of 2 health centers covering 2 sub-districts in South Nias. As many as 55 TB counselors have been trained and actively involved in conducting case discoveries in their respective villages. One of the material that should mastered by TB counselors is to use a scoring system in determining suspected child TB cases and then refer the patients to the health center for further treatment. Results: The involvement of TB counselors in the discovery of suspected child TB cases in their respective areas is expected to contribute to increase the number of case detection rate of child TB at the health center.Conclusion: There were no cases of child TB recorded at those 2 health centers before. Then, 3 cases reported in 2016. In 2017 there were 6 cases of child TB recorded in 2 health centers. This number increased to 12 in 2018. The cause of this increase is due to the involvement of TB counselors using a scoring system and applied referral mechanisms.